In Puppet Master’s Hand: Discursive Manipulation Strategies in Socio-semiotic Perspective - Dini Anggraheni; Anandha Anandha; Stefani Dewi Rosaria (Jurnal Lingua Idea, 2022)
Love has a huge impact on someone's life. To be in love, someone tries to find a romantic relationship. Indeed, romantic love can be developed without having frequent or real-life interactions, such as with a stranger from a dating app. Telecom and internet fraud has become a public hazard as a new type of contactless crime, with crooks targeting large numbers of unsuspecting victims. This paper linguistically investigates the main character of the Tinder Swindler documentary film. Simon, the main character discursive strategies designed to manipulate girls' minds into accepting, even doing anything that he says to get profit to fulfill his luxurious lifestyle. Regardless of the scientific and technological tools utilized by swindlers, language is the primary communication. From a socio-semiotic standpoint, this research shows that criminal suspects use discourse resources to fabricate false information and construct false identities through discursive practice, to gain victims' trust, trick, deceive, and manipulate them into giving out confidential information and funds. This study investigates the dynamic process of selecting and building identities in the social-cultural context by altering associated discourse resources and techniques. This research also offers a socio-semiotic strategy for preventing online and telecom scams. Keywords: discursive manipulation, film, identity, scam, socio-semiotic, dating application